(untitled) (Journal of Partial Differential Equations, 1990)
In this paper we discuss tbe local solvability of the following nonhomogeneous left invariant differential operators on the nilpotent Lie group H_n⊗R^K: P(X, Y, T, Z) = Σ_|α+β|+ζ+|y|≤m|α+β|+2l=aa_αβlyX^αY^βT^lZ^y where X_j, Y_j (j = 1, 2, …, n), T, Z_j(j = l, 2, …, K) are bases of left invariant vector fields on H_n⊗R^K and a_αβly are complex constants.